Dampak Penutupan Lokalisasi Kedungbanteng Terhadap Aspek Sosial Ekonomi Masyarakat - Erwin Andrianto; Nafiah Nafiah; Suad Fikriawan (Social Science Academic, 2025)
This article examines the impact of the closure of a localization area on the socioeconomic conditions of the community in Dukuh Kalipucang, Desa Kedungbanteng, Ponorogo Regency. This qualitative research aims to understand the social and economic changes that occurred in the community following the closure of the localization area, which previously served as a central economic hub for many local residents. Through in-depth interviews and direct observations, the study identifies various impacts of the localization closure, including changes in livelihood structures, shifts in social patterns, and effects on economic and social well-being. The findings indicate that the closure had a significant impact on the local economy, resulting in the loss of a primary source of income for many residents who depended on activities in the area. Additionally, the closure triggered shifts in social structures, such as changes in small business forms and increased reliance on social assistance. Although there have been efforts to address the negative impacts through economic diversification and skills training, challenges remain in terms of social adaptation and economic recovery. The study concludes that the closure of the localization area affects not only economic aspects but also the social dynamics of the community. The research employs a descriptive qualitative method, with data obtained through interviews. The findings show that the impacts of the localization closure are deeply felt by those who relied on the area for their livelihoods